2004
DOI: 10.1038/nature02838
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ultraviolet entangled photons in a semiconductor

Abstract: Entanglement is one of the key features of quantum information and communications technology. The method that has been used most frequently to generate highly entangled pairs of photons is parametric down-conversion. Short-wavelength entangled photons are desirable for generating further entanglement between three or four photons, but it is difficult to use parametric down-conversion to generate suitably energetic entangled photon pairs. One method that is expected to be applicable for the generation of such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
155
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 19 publications
1
155
0
Order By: Relevance
“…3. Due to the conservation of energy and wavevector, the positions of the two peaks depend on scattering angle, 10,11 and the entangled two photons are emitted symmetrical about the pump beam as shown in the inset. Two additional peaks called MT and ML in scattering spectra originate from the biexciton decay into transverse and longitudinal exciton levels, respectively.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Due to the conservation of energy and wavevector, the positions of the two peaks depend on scattering angle, 10,11 and the entangled two photons are emitted symmetrical about the pump beam as shown in the inset. Two additional peaks called MT and ML in scattering spectra originate from the biexciton decay into transverse and longitudinal exciton levels, respectively.…”
Section: Figmentioning
confidence: 99%
“…This second-order nonlinear process creates polarization-correlated entangled-photon pairs in nonlinear optical crystals with a birefringence. On the other hand, Savasta et al 12 suggested and Edamatsu et al 10 experimentally demonstrated that ultraviolet entangledphoton pairs are generated by the biexciton-resonant hy-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing HPS, in the future it will be possible to obtain a spatial resolution of 100 nm or below by using ultraviolet laser light. Recently we have successfully generated ultraviolet entangled photons, whose wavelength is approximately 390 nm, via HPS in a semiconductor crystal [26]. This may open the way to quantum imaging with truly high resolution beyond the classical limit.…”
Section: Fourier-optical Analysis Of a Two-photon Statementioning
confidence: 99%
“…Currently, there are a series of experimental techniques available to produce entangled photons such as parametric down conversion [10][11][12], four-wave mixing [13][14][15], electromagnetically induced transparency [16,17] or cavity QED [18,19]. Furthermore, an atomic memory for correlated photon states has been realized experimentally, playing an essential role for quantum communication over long distances [20][21][22]. Recently, a heralded entanglement source of great practical importance has been demonstrated [23,24].…”
Section: Introductionmentioning
confidence: 99%